Childhood Trauma and Chronic Illness in Adulthood: Mental Health and Socioeconomic Status as Explanatory Factors and Buffers - Mock, Steven E.; Arai, Susan M. (Frontiers in Psychology, 2011)
Experiences of traumatic events in childhood have been shown to have long-term consequences for health in adulthood. With data from the 2005 Canadian Community Health Survey we take a life course perspective of cumulative disadvantage and examine the potential role of mental health and socioeconomic status in adulthood as multiple mediators of the link between childhood trauma and chronic illness in adulthood. Mental health and socioeconomic status are also tested as buffers against the typically adverse consequences of childhood trauma. The results suggest mental health and socioeconomic status partially explain the association of childhood trauma with chronic illness in adulthood, with mental health showing a stronger effect. In addition, an analysis of the interactions suggested higher socioeconomic status is a potential protective factor for those with a history of trauma. Results also suggest cumulative disadvantage following trauma may lead to chronic illness and suggest the need for public health expenditures on resources such as counseling and income supports to prevent or reduce psychological harm and chronic illness resulting from traumatic events.